Analisis Pelaksanaan Program Keaksaraan Dasar Di PKBM Ina Malaka Kecamatan Malaka Barat Kabupaten Malaka - Bria, Yunita Namok; Ray, Fransiskus F. G; Syukur, Abdul; Simbolon, Gallex (Education For All, 2025)
Background Education is the main thing in the current era of globalization.Education in the era of globalization emphasizes the development of futureoriented education. Education cannot be separated from the existence ofknowledge, skills and creativity which actually aims to equip children to facecurrent developments. Data on illiteracy taken by researchers on October 25 2022 at the Malacca Regency education office found that the number ofilliterates in 2022 will be 500 illiterates. The aim is to analyze theimplementation of the basic literacy program at PKBM Ina Malaka and theimpact of implementing the literacy program. The method used is aqualitative method. The technique used to collect data is interviews. As aresult of the research, several findings can be found, namely that theimplementation of the basic literacy program carried out by PKBM InaMakala was carried out in several stages, namely the planning stage,implementation stage, evaluation stage, in carrying out the program. Apartfrom that, many people are enthusiastic about implementing basic literacylearning so that all learning citizens get a literacy certificate (SUKMA) eventhough the infrastructure is still simple in the form of writing tools but alreadysupports the basic literacy program process. PKBM Ina Malaka has had adecreasing impact on illiterate people in West Malaka District, MalakaRegency